THE EFFECTS OF BAROQUE MUSIC EXPOSURE ON STUDENTS DURING WRITING A NARRATIVE TEXT - Iqbal Fatwa Resmana; Anita Anggraeni (Universitas Brawijaya, 2018)
This research aims to uncover the effects of Baroque music exposure on students during a narrative writing, and is motivated through the popular beliefs of Mozart effect which can enhance human’s intelligence and performance in cognitive tasks. This research is conducted from January 18 until February 15, 2018. This research is presented by using qualitative design and method to describe and analyse the result of the interview. The population in this research is the eleventh grader students of Math and Science-1 of State Senior High School 1 Gununghalu and there are three interviewees. This research uses description and interpretation technique data analysis. The findings show that the exposure of Baroque music during the narrative writing activity gives positive effects to 66% of the participants. It helps them to relax and to soothe their emotional state, and eventually affects their brain activity to create imagery visions. However, it can also be harmful to others, where 34% of the participants consider the music as a distraction to their activity and reducing their concentration. In the end, the result of the participants’ writing products is determined through additional factors and conditions besides music.